2022
DOI: 10.1101/2022.09.25.22280333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post COVID-19 condition after Wildtype, Delta, and Omicron variant SARS-CoV-2 infection and vaccination: pooled analysis of two population-based cohorts

Abstract: Background: Post COVID-19 condition (PCC) is an important complication of SARS-CoV-2 infection, affecting millions worldwide. Further evidence is needed on the risk of PCC after vaccination and infection with newer variants. This study aimed to evaluate the prevalence and severity of PCC across different variants and vaccination histories. Methods: We used pooled data from 1350 SARS-CoV-2-infected individuals from two representative population-based cohorts in Switzerland, diagnosed between Aug 5, 2020, and Fe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This nding is in line with previous studies showed that the risk of post-COVID complaints are differed as function of vaccinate status. In that, post-COVID complaints are more common in non-vaccinated individuals compared to vaccinated individuals 45,47,48,49,50,51,52,53 . In the current study, been hospitalized didn't contribute to the explained variances in post-COVID impairments.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This nding is in line with previous studies showed that the risk of post-COVID complaints are differed as function of vaccinate status. In that, post-COVID complaints are more common in non-vaccinated individuals compared to vaccinated individuals 45,47,48,49,50,51,52,53 . In the current study, been hospitalized didn't contribute to the explained variances in post-COVID impairments.…”
Section: Discussionmentioning
confidence: 94%
“…It is well established that early variants of SARS-CoV-2 in prior waves appeared to cause more severe acute illness than later variants 43,44 . Moreover, recent studies showed that the prevalence and pro le associated with post-COVID condition vary across different SARS-CoV-2 variants 44,45,46 . It is therefore reasonable to conclude that those infected in the early waves of pandemic in Sweden continue to be a vulnerable group to have more severe complaints due to COVID-19 infection and in need of support.…”
Section: Discussionmentioning
confidence: 99%
“…In previous waves, including the Delta variant and those preceding Omicron, a significant number of individuals were not vaccinated. However, vaccination, particularly booster shots, plays a crucial role in providing protection against severe Omicron infections and the need for hospitalization [ 25 , 26 , 27 , 28 ]. Nevertheless, the vaccination data within our study are limited, given the relatively high number of unreported cases.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, prevalence of at least one possible PCC-related symptom was similar between both groups. Studies have shown a partial protection of the primary course compared to unvaccinated cases for pre-Omicron variants (8,30,31) and for Omicron (32). Research on the effect of the booster is limited but one study shows a lower association with PCC for threedose vaccinated Omicron cases compared to two-dosed (23).…”
Section: Discussionmentioning
confidence: 99%